2001
DOI: 10.1074/jbc.m010048200
|View full text |Cite
|
Sign up to set email alerts
|

Hypersulfated Low Molecular Weight Heparin with Reduced Affinity for Antithrombin Acts as an Anticoagulant by Inhibiting Intrinsic Tenase and Prothrombinase

Abstract: In buffer systems, heparin and low molecular weight heparin (LMWH) directly inhibit the intrinsic factor Xactivating complex (intrinsic tenase) but have no effect on the prothrombin-activating complex (prothrombinase). Although chemical modification of LMWH, to lower its affinity for antithrombin (LA-LMWH) has no effect on its ability to inhibit intrinsic tenase, N-desulfation of LMWH reduces its activity 12-fold. To further explore the role of sulfation, hypersulfated LA-LMWH was synthesized (sLA-LMWH). sLA-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 55 publications
6
31
0
Order By: Relevance
“…However, because heparin has a lower affinity for the 162-loop of FXa, it may not efficiently compete with factor Va/prothrombin for binding to this site of the protease and thus is unable to directly inhibit the prothrombinase complex. In support of this hypothesis, a recent study demonstrated that a hypersulfated heparin, which has an improved affinity for interaction with these proteases, is effective in directly inhibiting both the intrinsic and prothrombinase complexes independent of membrane surfaces (33). These results can best be described by a model in which hypersulfated heparin disrupts the assembly of activation complexes by competing with specific cofactors and/or substrates of FIXa and FXa for binding to the 162-loop of these procoagulant proteases.…”
Section: Discussionmentioning
confidence: 55%
“…However, because heparin has a lower affinity for the 162-loop of FXa, it may not efficiently compete with factor Va/prothrombin for binding to this site of the protease and thus is unable to directly inhibit the prothrombinase complex. In support of this hypothesis, a recent study demonstrated that a hypersulfated heparin, which has an improved affinity for interaction with these proteases, is effective in directly inhibiting both the intrinsic and prothrombinase complexes independent of membrane surfaces (33). These results can best be described by a model in which hypersulfated heparin disrupts the assembly of activation complexes by competing with specific cofactors and/or substrates of FIXa and FXa for binding to the 162-loop of these procoagulant proteases.…”
Section: Discussionmentioning
confidence: 55%
“…Agents that disrupt these activation complexes may then permit greater access of antithrombin to the protease components. HS-LMWH fits this description as it disrupts both prothrombinase and intrinsic tenase complexes, likely by binding to the heparin-binding sites on f.Xa and f.IXa, respectively (31). Therefore, the heparin-binding site on f.IXa plays an important physiological role that may be exploited for therapeutic purposes.…”
Section: Physiological Considerations and Implicationsmentioning
confidence: 99%
“…Binding Experiments-The affinity of fluorescein-HS-LMWH for f.IXa was measured as previously described and competition experiments were then performed to determine the affinities of heparin and fondaparinux for f.IXa (31). Briefly, the affinity of fluorescein-HS-LMWH for f.IXa was determined by monitoring fluorescence of a titration of fluorescein-HS-LMWH with f.IXa.…”
Section: Analysis Of Fii Fix and Fx Activation And Subsequent Inmentioning
confidence: 99%
“…Sulfatases hydrolytically remove the sulfuryl moiety to regenerate unmodified acceptors, and the balance of SULT and sulfatase activities determines the sulfation status of a given small molecule (7). Sulfation is critical to normal functioning of a variety of processes including hemostasis (8), immune system recognition (9), lymph circulation (10), pheromone signaling (11), and growth factor recognition (12). Given its many functions in metabolism, it is not surprising that sulfonation imbalances are linked to human diseases, which include cancer of the breast and endometrium (13,14), Parkinson disease (15), cystic fibrosis (16), and hemophilia (17).…”
mentioning
confidence: 99%